Risperidone in the treatment of conduct disorder in preschool children without intellectual disability - Durak Sibel; Basay Omer; Basay Burge; Ercan Eyup S; Ozbaran Burcu (BMC, 2011)
Abstract Background The DSM-IV-TR (Diagnostic and Statistical Manual of Mental Disorders, 4th edition Textrevision) highlights the especially poor outcomes of early-onset conduct disorder (CD). The strong link between the patient's age at treatment and its efficacy points the importance of early intervention. Risperidone is one of the most commonly studied medications used to treat CD in children and adolescents. The aim of this study is to obtain preliminary data about the efficacy and tolerability of risperidone treatment in otherwise typically developing preschool children with conduct disorder and severe behavioral problems. Method We recruited 12 otherwise normally developing preschoolers (ten boys and two girls) with CD for this study. We could not follow up with 4 children at control visits properly; thus, 8 children (six girls, two boys; mean age: 42.4 months) completed the study. We treated the patients with risperidone in an open-label fashion for 8 weeks, starting with a daily dosage of 0.125 mg/day or 0.25 mg/day depending on the patient's weight (<20 kg children: 0.125 mg/day; >20 kg children: 0.25 mg/day). Dosage titration and increments were performed at 2-week interval clinical assessments. The Turgay DSM-IV Based Disruptive Behavior Disorders Child and Adolescent Rating & Screening Scale (T-DSM-IV-S) as well as the Clinical Global Impression Scale (CGI) assessed treatment efficacy; the Extrapyramidal Symptom Rating Scale (ESRS) and laboratory evaluations assessed treatment safety. Results The mean daily dosage of risperidone at the end of 8 weeks was 0.78 mg/day (SD: 0.39) with a maximum dosage of 1.50 mg/day. Based on the CGI global improvement item, we classified all patients as "responders" (very much or much improved). Risperidone was associated with a 78% reduction in the CGI Severity score. We also detected significant improvements on all of the subscales of the T-DSM-IV-S. Tolerability was good, and serious adverse effects were not observed. We detected statistically significant prolactin level increments (p < 0.05), but no clinical symptoms associated with prolactinemia. Conclusion The results of this study suggest that risperidone may be an effective and well-tolerated atypical antipsychotic for the treatment of CD in otherwise normally developing preschool children. The findings of the study should be interpreted as preliminary data considering its small sample size and open-label methodology.